THE VALUES OF BUREAUCRACY - Paul du Gay (University of Oxford., 2005)
The chapters in this volume derive from a workshop on ‘Defending Bureaucracy’ held at St. Hugh’s College, Oxford, in March, 2003. I would like to thank everyone who participated in the workshop and to offer my considerable gratitude to Pamela Walker and Karen Ho, who helped organize the event and ensured its smooth running. The workshop would not have been possible without the generous financial support of the Pavis Centre for Social and Cultural Research at the Open University. The preparation of this volume was greatly facilitated by the support of the Department of Organization and Work Sociology (IOA) at the Copenhagen Business School where the editor spent some time as a Visiting Scholar in 2003. Finally, a word of gratitude to David Musson for commissioning the volume and to Matthew Derbyshire for editorial guidance, to the chapter authors who have borne stoically the successive rounds of alterations and amendments, and to Denise Janes, of the Centre for Citizenship, Identities and Governance at the Open University, for her exceptional administrative and secretarial support